Phase relations between Na3Nd(BO3)2, Na3Nd2(BO3)3, NdBO3 and their luminescence properties - Kuznetsov, Artem B.; Jamous, Ammar Y.; Svetlichnyi, Valerii A.; Kokh, Konstantin A. (Journal of structural chemistry)
The Na3Nd(BO3)2-NdBO3 phase diagram was investigated by the solid-state synthesis and DSC methods. Na3Nd(BO3)2, Na3Nd2(BO3)3 and NdBO3 were grown by spontaneous crystallization from the Na2O-B2O3- NaF flux. Typical Nd3+ luminescence of 4F3/2 → 4I9/2 and 4F3/2 → 4I11/2 electron transitions at 875 nm and 1054 nm were registered. Maximum integral intensity of the luminescence was observed for Na3Nd2(BO3)3 crystals, more than twice that of NdBO3, Na3Nd(BO3)2.